ANALISIS SISTEM PENGELOLAAN PETERNAKAN AYAM PETELUR: STUDI KASUS ASPEK LINGKUNGAN, KESEHATAN, DAN PRODUKTIVITAS DI SKALA PETERNAKAN MENENGAH - Ananda Purnomo; Tia Meylan Anggraeni; Eko Prihandono; M. Barkah Salim (Universitas Muhammadiyah Metro, 2026)
Abstract: This study aims to analyze the management system of medium-scale layer chicken farms, focusing on aspects of feed management, animal health, waste handling, and adaptation to environmental conditions. The research employed a qualitative descriptive approach through a case study and in-depth interviews with an independent farmer. The results showed that although modern technology was not applied, disciplined and adaptive farm management practices maintained a high egg productivity of around 700 eggs per day. The farmer implemented a feeding schedule three times a day, maintained cage hygiene, and regularly conducted vaccinations and preventive treatments. The main challenge was extreme temperatures causing chicken stress and reduced productivity, which was addressed by reducing cage density and increasing water supply frequency. Waste handling was carried out manually with disinfectant spraying to minimize odor and disease risk. In conclusion, medium-scale layer chicken farms have significant potential to support local food security if supported by proper training and appropriate low-cost technological innovations.